Expression of lymphatic markers in angiokeratomas. (6th May 2014) - Wang, Lei; Yuan, Wei; Geng, Songmei; Xiong, Ya; Zhang, Dezhi; Zhao, Xiaoqing; Li, Shenqiu; Bi, Xinling; Gao, Tianwen; Wang, Gang
<x xml:space="preserve">Abstract</x> Background The term angiokeratoma refers to a group of unrelated diseases with similar histopathologic features. Four clinical variants of angiokeratoma have been described. However, it is not known whether some variants of angiokeratoma are of lymphatic origin, and an immunohistochemical study of lymphatic markers has not been previously performed. Methods We performed an immunohistochemical study of angiokeratomas using lymphatic markers. Fifteen cases of angiokeratoma corporis diffusum, 10 cases of Fordyce angiokeratoma, 10 cases of Mibelli angiokeratoma and 10 cases of solitary angiokeratoma were examined by immunohistochemical analysis using CD31, D2‐40, Prox1 and Wilms' tumor 1 (WT‐1). Results The vessels of angiokeratoma corporis diffusum, Fordyce angiokeratoma and solitary angiokeratoma were usually focally positive for D2‐40 and positive for Prox1, whereas the vessels of Mibelli angiokeratoma were negative for D2‐40 and positive for Prox1. Conclusions The results suggest lymphatic derivation of angiokeratoma corporis diffusum, Fordyce angiokeratoma and solitary angiokeratoma. However, the derivation of Mibelli angiokeratoma could not be determined based on the present immunohistochemical results.